2017
DOI: 10.1111/ajt.14048
|View full text |Cite
|
Sign up to set email alerts
|

Early Conversion to Prednisolone/Everolimus as an Alternative Weaning Regimen Associates With Beneficial Renal Transplant Histology and Function: The Randomized-Controlled MECANO Trial

Abstract: In renal transplantation, use of calcineurin inhibitors (CNIs) is associated with nephrotoxicity and immunosuppression with malignancies and infections. This trial aimed to minimize CNI exposure and total immunosuppression while maintaining efficacy. We performed a randomized controlled, open-label multicenter trial with early cyclosporine A (CsA) elimination. Patients started with basiliximab, prednisolone (P), mycophenolate sodium (MPS), and CsA. At 6 months, immunosuppression was tapered to P/CsA, P/MPS, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 32 publications
3
36
0
Order By: Relevance
“…Moreover, in the present study, we further studied our patient populations and identified triggering factors, such as infection, surgical procedures, or increased plasma levels of factor VIII, that may have induced these thromboembolic complications. The 24‐month randomized controlled Mycophenolate sodium vs. Everolimus or Cyclosporine with Allograft Nephropathy as Outcome (MECANO) trial of the administration of EVR to renal transplant recipients found more cardiovascular complications and more events of venous thrombosis and lung embolus among the patients treated with EVR in combination with prednisone; these results confirm those of our study . Even so, our study is a retrospective analysis with all of the common limitations of this study design, such as the various observational times of the groups, and these limitations may bias the results.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Moreover, in the present study, we further studied our patient populations and identified triggering factors, such as infection, surgical procedures, or increased plasma levels of factor VIII, that may have induced these thromboembolic complications. The 24‐month randomized controlled Mycophenolate sodium vs. Everolimus or Cyclosporine with Allograft Nephropathy as Outcome (MECANO) trial of the administration of EVR to renal transplant recipients found more cardiovascular complications and more events of venous thrombosis and lung embolus among the patients treated with EVR in combination with prednisone; these results confirm those of our study . Even so, our study is a retrospective analysis with all of the common limitations of this study design, such as the various observational times of the groups, and these limitations may bias the results.…”
Section: Discussionsupporting
confidence: 85%
“…Currently, EVR is commonly used after LT because of its beneficial nephroprotective, antiviral, and antiproliferative effects . Sirolimus has received black‐box warnings related to death and graft loss in LT, and concerns have thus been raised about mTOR inhibitors regarding thromboembolic complications mainly on the basis of studies showing an increased thromboembolic risk for sirolimus . In lung transplant recipients, sirolimus caused an increased risk for venous thromboembolism, whereas in LT patients, sirolimus was responsible for a higher incidence of artery and portal vein thrombosis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EVE is successfully used in combination with cyclosporine and corticosteroids both in adult and paediatric population of renal- and cardiac-transplant recipients, but far less often for lung-transplant recipients [4,5,6,7]. Particularly for these patients, survival continues to be challenged by chronic allograft dysfunctions, such as obliterative bronchiolitis or its clinical correlate bronchiolitis obliterans syndrome (BOS), a fibrous obliteration of small airways caused by mesenchymal cells (MSc) abnormal proliferation, and extracellular matrix deposition causing bronchiolar occlusion and organ rejection [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%